GROWING COMMUNITY CARE FOR A CLEAN AND WASTE-FREE ENVIRONMENT IN PONDOK BAMBU VILLAGE, DUREN SAWIT DISTRICT, EAST JAKARTA - Edison Hatoguan Manurung; Bantu Hotsan Simanullang; Pahala Sinambela; Andri Waskito; Parulian Naibaho; Herbert Hasudungan Siahaan (Yayasan Education and Social Center, 2022)
The application of a clean and healthy lifestyle should become a daily habit. Management is fully felt by humans, management in the utilization of natural resources in addition to promoting general welfare as well as to achieve happiness in life and the way of its efforts must pay attention to the preservation of the ability of the living environment in a harmonious and balanced manner to support sustainable development. The purpose of this activity is to create a sense of community concern for a clean and waste-free environment. Meanwhile, the benefit of this activity is to raise public awareness of Pondok Bambu Village, Duren Sawit District, East Jakarta or those who are not in the area so as not to litter. Program activities carried out through 1) Physical group programs, namely the creation of a sign appealing to the community to always keep the environment clean and the provision of trash bins for the surrounding community, so that they can always maintain the cleanliness of the local environment in order to create a clean, tidy and free of waste environment. 2) Non-physical group programs, namely: carrying out mutual cooperation activities to clean the environment to provide an example to the local community so that it can create a sense of empathy for the local community towards environmental cleanliness. 3) Additional group programs, namely: holding a simple event to inaugurate and legalize the installation of signs and trash bins which were inaugurated and legalized by all regional officials